Political behavior does not (always) undermine strategic decision making: Theory and evidence - Shepherd, Neil Gareth; Hodgkinson, Gerard P.; Mooi, Erik A.; Elbanna, Said; Rudd, John Maynard (Long range planning, 2020)
Political behavior pervades strategic decision-making, often damaging decision quality and undermining organizational performance. However, little is currently known about how top management teams (TMTs) cope with such behavior. To address this shortfall, we draw on the upper echelons literature to advance a contingent account of the factors that differentiate well-functioning and dysfunctional TMTs. Focusing on the psychological context surrounding the TMT, we theorize that cognitive consensus, power decentralization, and behavioral integration are key generative mechanisms that enable TMTs to countermand the potentially deleterious consequences of political behavior. We corroborate our theorizing using a field study of 117 strategic decisions, drawn from multiple TMT informants and secondary databases. Confirming the majority of our hypotheses, our findings indicate that behaviorally integrated and decentralized TMTs are better equipped to attenuate the potentially damaging effects of organizational politics, thereby safeguarding the quality of their decision processes.